HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN CHEST PASS PADA TIM BOLA BASKET PUTRI SMA NEGERI 3 PEKANBARU - Haniva Wisdarti; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : the problem of this study is the lack of ability chest pass in basketball women’s team senior high school 3 Pekanbaru. It is thought to because of the lack of arm and shoulder muscle strenght and hand-eye coordination when doing chest pass, The purpose of this research to determine the reletionship of the arm and shoulder muscle strenght and hand-eye coordination withthe chest pass ability.This is correlational study that aimed to know how big the contribution between independent and dependent variables. After that, conducted data normality test by liliefors test with significant level α= 0,05, and the result for normality test of X1 variable is Lomax (0,108) < Ltable (0,220) ,and the result for normality test of X2 variable is Lomax (0,1348) < Ltabel (0,220 ), normality test of Y variable Lomax (0,1332)<Ltable(0,220). in other words, the distribution of the data is normal. Then, continued by determining the r using product moment correlational analysis. If rresult > rtable then the result is, there is significant relitionship on it. From the calculation of the correlation between the strenght of the arm and shoulder muscles with the chest pass ability is obtained rhitung = 0,556 while rtable =0,532. The result of calculation of corelation between hand-eye coordination with the chest pass ability is obtained rresult =0,572 while rtable = 0,532. To determine the R variables X1 and X2 with Y performed using double formula, with rhitung = 0,632 > rtable = 0,532. So, Ho is refused and Ha is accepted. Based on the research result,the conclusion is there is significant relationship between arms and shoulder muscle strenght and hand-eye coordination with the ability chest pass in basketball women’s team senior high school 3 Pekanbaru.keyword: Arm And Shoulder Muscle Strenght, hand-eye coordination, chest pass